Morpho-physiological characteristics, selected macronutrient uptake, and oxidative stress level of andrographis paniculata under saline condition - Ismail, Nor Adibah; Hossain, Md Sanower; Mohd Mustafa, Nurhidayatul Husna; Phang, Ing Chia (Universiti Teknologi Malaysia, 2015)
Andrographis paniculata (Hempedu Bumi) is an important therapeutical herb that tends to be affected by salinity stress, leading to reduction of plant productivity and growth. This study aimed to study the effects of salt stress on the morpho-physiology, selected macronutrients uptake, as well as intensity and localization of reactive oxygen species in A. paniculata. Symptoms of salt toxicity were observed on A. paniculata including dehydration and browning of leaves. Na+ content in plants was significantly increased as NaCl concentration increases, while K+ content was significantly reduced. For Ca2+ and Mg2+ content, no significant difference was detected between control and plants treated with 92.40 mM NaCl. Histochemical staining showed that the accumulation of superoxide in 41.10 mM salt-treated leaves was higher than the control, whereas no differences were found for hydrogen peroxide. A. paniculata appeared to be affected by saline condition.